Pengaruh Penerapan Model Debat Terhadap Hasil Belajar PAI Siswa Kelas XI Di SMAN 3 Payakumbuh - Angga Ramadhan; Charles Charles; Arifmiboy Arifmiboy; Iswantir M (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This research is motivated by the many learning models put forward by educational experts to realize the achievement of learning objectives. One of the learning models is the Debate learning model. Learning Islamic Religious Education at SMAN 3 Payakumbuh City, especially in class XI, uses a conventional learning model, namely a learning model that refers to teachers in conveying learning, but it is not optimal. This can be seen from the low student learning outcomes. The average value of students' daily tests has not yet reached the Minimum Completeness Criteria (KKM) that has been set. Seeing this incident, the researcher is interested in conducting research by seeing whether there is an influence of the debate learning model on student learning outcomes in Islamic religious education subjects at SMAN 3 Payakumbuh City. The hypothesis in this study is that the learning outcomes of Islamic religious education using the debate learning model are better than the learning outcomes of Islamic religious education using the conventional model at SMAN 3 Payakumbuh City. This type of research is quasy experiment with pretest-posttest control group design. The population in this study were 138 students of class XI IPS, consisting of 4 normal and homogeneous locales. The sample in this study was class XI IPS 5 as the experimental class and class XI IPS 1 as the control class. The data obtained from the results of this study were processed using the t-test, after analysis, it was obtained that tcount was 2.12935 and ttable value = 1.67109. Thus, tcount > ttable was 2.12935 and > 1.67109 at the significant level  = 0 .05, means the hypothesis is accepted. So it can be concluded that the learning outcomes of students who use the Debate model are better than the learning outcomes of students who use the Conventional learning model.